Enhanced Heat Transfer Analysis on MHD Hybrid Nanofluid Flow Over a Porous Stretching Surface: An Application to Aerospace Features - R. Chandra Sekhar Reddy; Ramasekhar Gunisetty (East European Journal of Physics, 2023)
The advancement of aircraft technology has presented manufacturers with new criteria and problems for the functioning of their devices. It is essential that, in order to guarantee the secure operation of aerospace machinery, the failure mechanisms be identified and the operational durability of critical structural components be improved as quickly as possible. New aviation materials have been developed in modern years. In an aviation engine, engine oil lubricates, cools, washes, maintains against rust, decreases sound, and accelerates. Most important is lubrication. All mechanical components would burn out if not maintained. The aim of this work is to minimize costs by extending the operational life of aircraft components (mechanical and motor parts) and enhancing fuel mileage and flying distance. Based on the importance of the inspiration on magnetohydrodynamic Aluminum Oxide-Cobalt hybrid nanofluid flow over a stretching surface (SS) in the existence of porous medium, and thermal radiation are investigated. In this model we used Engine oil mixed with Aluminum Oxide and Cobalt nanoparticles. By using the suitable self-similarity variables, the PDE is transformed into ODEs. After then, the dimensionless equations are solved by using the Maple built in BVP Midrich scheme. Graphs and tables explain how the operational factors affect fluid flow efficiency. Compared to nanofluids, hybrid nanofluids have a better heat transfer rate.